Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Kota Jati Furindo Jepara - Aisyah Intan Harisha; Arif Partono Prasetio (STIE Mandala Jember, 2023)
Organization need to increase their employee performance. Employee performance in company has an important role to improve and advance company’s business. In order to increase their employee performance, organization need to know factors that influence employee performance. Work Dsicipline is one of the important factor that can predict employee performance. This study is aimed to identify the impact of work discipline on employee performance in PT Kota Jati Furindo Jepara. Hypothesis for this research is work discipline has significant effect on employee performance. This research use quantitatve approach. The questionnaire was distributed to 350 employee PT Kota Jati Furindo Jepara and gets 313 useable responses. Using simple regression and decriptive methode, we found that work discipline has significant positive effect on employee performance (0,551). This finding is in line with previous research that work discipline has positive and significant effect on employee performance.